Medical аnd еconomic аspects оf the use of vacuum therapy for esophageal injures - Damir A. Demaldinov; Robert D. Mustafin (ZAO "Consilium Medicum", 2024)
Background. Currently, endoscopic vacuum therapy (EVT) with an efficiency of up to 90% or more is actively used in the treatment of esophageal injuries. At the same time, the economic assessment of the advantages of minimally invasive methods has not been studied enough. Aim. To Analysis of the economic component of EVT for esophageal injuries in comparison with classical interventions (thoracotomy, esophageal extirpation) in a regional multidisciplinary hospital. Materials and methods. The analysis of the economic component of EVT in comparison with classical interventions was carried out by retrospectively examining the medical records of 43 patients. The cost of treatment in the comparison groups was estimated by including the cost of the patient's stay in the hospital and the direct costs of intervention. Results. The conducted statistical analysis showed significant differences in the groups with a strong dependence of the cost of treatment on the patient's stay in the intensive care units and the direct costs of open surgery. Conclusion. The use of minimally invasive and modern EVT methods for esophageal injuries can significantly shorten the patient's hospital stay. Compared to traditional surgical approaches, this approach allows for a reduction in the financial aspect by more than two times.